Testicular morphometry during the reproductive cycle of Dendropsophus minutus (Peters) (Anura, Hylidae) - Santos, Lia R. de S.; Oliveira, Classius de (Soc Brasileira Zoologia, Univ Federal Parana, 2007)
This study describes the male reproductive cycle of Dendropsophus minutus (Peters, 1872) based on testicular morphometric analysis, related to climatic conditions. Fifty individuals where collected in Sao Jose do Rio Preto, Sao Paulo. After macroscopic analysis, the testes were submitted to histological routine, fixed with Bouin, embedded in historesin. Sections of 2 pm were stained with 1% toluidine blue and observed to the microscope. The testes of A minutus are small organs (length 1.90 +/- 0.13 mm), whitish, oviform and found in the abdominal cavity. They are located in the cranial extremity of the kidneys and present asymmetry as far as position. According to statistical analyses, there is no intra-individual variation in length and weight of the testes, as well as in the area and diameter of the seminiferous locules. Concerning the testicular histology, it was possible to identify, throughout the year, in seminiferous locules, all the cellular types from the spermatogenic lineage, characterizing a continuous gametogenesis, corroborated by ecological and behavioral factors. Information about testicular morphometry and reproductive cycle has important biological value for anurans in the neotropics.
Keywords: anuran; reproduction; spermatogenesis; testis